Clinical Trial Designs for Neuromodulation in Chronic Spinal Cord Injury Using Epidural Stimulation. Issue 3 (1st April 2021) - Boakye, Maxwell; Ugiliweneza, Beatrice; Madrigal, Fabian; Mesbah, Samineh; Ovechkin, Alexander; Angeli, Claudia; Bloom, Ona; Wecht, Jill W.; Ditterline, Bonnie; Harel, Noam Y.; Kirshblum, Steven; Forrest, Gail; et al.
Abstract: Study Design: This is a narrative review focused on specific challenges related to adequate controls that arise in neuromodulation clinical trials involving perceptible stimulation and physiological effects of stimulation activation. Objectives: 1) To present the strengths and limitations of available clinical trial research designs for the testing of epidural stimulation to improve recovery after spinal cord injury. 2) To describe how studies can control for the placebo effects that arise due to surgical implantation, the physical presence of the battery, generator, control interfaces, and rehabilitative activity aimed to promote use‐dependent plasticity. 3) To mitigate Hawthorne effects that may occur in clinical trials with intensive supervised participation, including rehabilitation. Materials and Methods: Focused literature review of neuromodulation clinical trials with integration to the specific context of epidural stimulation for persons with chronic spinal cord injury. Conclusions: Standard of care control groups fail to control for the multiple effects of knowledge of having undergone surgical procedures, having implanted stimulation systems, and being observed in a clinical trial. The irreducible effects that have been identified as "placebo" require sham controls or comparison groups in which both are implanted with potentially active devices and undergo similar rehabilitative training.